COMMON FIXED POINTS FOR WEAKLY COMPATIBLE MAPS IN INTUITIONISTIC FUZZY METRIC SPACES USING PROPERTY (S-B) - Sharma, P. K.; Sharma, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this note we prove a common fixed point theorem for weakly compatible maps in intuitionistic fuzzy metric spaces using property (S-B), which generalize the results of Kumar and Vats [26], Alaca, Turkoglu and Yildiz [5].